News Site as Virtual Linguistic Landscape: Representation on Linguistic Landscape and Multimodal Discourse Analysis - Permana, Putu Gede Angga Mahaputra; Ma, Ling; Firdha Insani, Kania; Rusmawati, Roosi (Alphabet, 2023)
This study explores the linguistic landscapes of virtual news articles and aims to determine the websites' choice of language from the linguistic perspective as well as to understand what distinct visual components are highlighted within the websites. This includes how the virtual linguistic landscape of news websites reflects cultural, political, and social ideologies; and examines how linguistic choices and multimodal elements influence the framing of news, the construction of identity, and the negotiation of power dynamics. The data for the study consists of five different international news sites which utilize English as the primary language. The study utilizes principles of Multimodal Discourse Analysis (MDA) and Linguistic Landscape (LL) theory from Pauwels (2012). By understanding how news organizations leverage the virtual linguistic landscape, we gain a deeper understanding of the dynamics that shape our contemporary information landscape and how language and visuals influence public discourse and collective comprehension.